Water Level Data Acquisition System Using Ultrasonic Waves Based On Internet of Things for Open Channel Flow Rate Prediction - HARDI (NIM : 13313087) - NIZAR GHOZALI (NIM : 13313094), VIANKA
Micro Hydro Power (MHP) Plant is a hydro power plant with a scale of 5 - 100 kW. Prior to installation of the plant, it is necessary to conduct a hydrological survey to obtain the river flow rate within a certain period of time which is generally a year. Variations of river flow rate data function to determine the type of turbine used in accordance with river energy capacity. In this study, the design and implementation of internet-based data acquisition system for measuring the river flow in real-time automatically was performed. The measurement of the flow rate was conducted using an indirect method that determine the flow rate by only measuring the water level. The water level is calculated using ultrasonic waves and then transmitted using internet network with Message Queue Telemetry Transport (MQTT) data communication protocol. From the experimental results, the accuracy of ultrasonic sensor is 97.7% - 99.64% and the precision is 99.4% - 99.75%. Meanwhile, in the data transmission experiment, there was lost data on the 3G network of 0.3% with bandwidth consumption of 154.8 byte/data. Thereafter, an experiment to compare the flow rate measurement using the indirect method with the direct method was implemented. The indirect method was applied using Manning equation, whereas the direct method was executed using area-velocity method. The experimental results show that flow rates measured using Manning equation that was integrated with data acquisition system has an error rate of 2.76% - 9.98% which is relatively small when compared with the error rate in the area-velocity method which has a range of 0.4% - 20.08%.